2011
DOI: 10.1080/01431161.2011.630331
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the activity of a large landslide in southern Italy by ground-monitoring and SAR interferometric techniques

Abstract: Landslides are recognized as one of the most damaging natural hazards in Italy. Campania region represents a complex geological setting, where mass movements of different types are widespread, and urban expansion can be increasingly seen by the presence of buildings and infrastructure in landslide-prone areas. In such a context, monitoring of unstable slopes represents a key activity in the process of landslide risk prevention and mitigation, in order to correctly establish a cause-effect correlation and to pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
49
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 69 publications
(49 citation statements)
references
References 31 publications
0
49
0
Order By: Relevance
“…The outcomes of this work suggest that the PSI technique can have a high potential in the field of landslide monitoring, but the use of only this technique for this purpose needs to be carefully evaluated [58]. Even if the use of the PSI technique can overcome some limitations of the conventional monitoring techniques (e.g., large extension of the area to be monitored and high costs, inaccessibility of the area, problems of installation and maintenance) it cannot replace in situ measurements [58].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The outcomes of this work suggest that the PSI technique can have a high potential in the field of landslide monitoring, but the use of only this technique for this purpose needs to be carefully evaluated [58]. Even if the use of the PSI technique can overcome some limitations of the conventional monitoring techniques (e.g., large extension of the area to be monitored and high costs, inaccessibility of the area, problems of installation and maintenance) it cannot replace in situ measurements [58].…”
Section: Discussionmentioning
confidence: 99%
“…Even if the use of the PSI technique can overcome some limitations of the conventional monitoring techniques (e.g., large extension of the area to be monitored and high costs, inaccessibility of the area, problems of installation and maintenance) it cannot replace in situ measurements [58].…”
Section: Discussionmentioning
confidence: 99%
“…Similar approaches have been used to map the state of activity or hazard of a specific landslide [5,[11][12][13]; the novelty of this study resides in the long-term multitechnological monitoring of the landslide and on the particular location of the phenomenon that affects the expansion of a major touristic area listed in the UNESCO world heritage sites. Most of the time, literature focuses on the problems carried by anthropic pressure in developing countries, however, even in parts of Europe there is pressure to construct on landslides.…”
Section: Introductionmentioning
confidence: 99%
“…Thirdly, PSI is effective for investigating landslide mechanism. For example, Hilley et al [27] performed one of the earliest studies to analyze landslide dynamics from PS and precipitation data; Colesanti and Wasowski [28] integrated field investigation with acquisition geometry to understand landslide mechanism in Liechtenstein Alps; Calo et al [29] exploited PS combined with ground measurements to assess the activity of landslides; Zhao et al [30] attempted to understand mechanism of slope failure and define corresponding rainfall thresholds for landslide early warning purposes by using PS covering California and Oregon, USA. Other representative applications of PSI in landslide studies include: Cascini et al [31] suggested to project the line-of-sight (LOS) deformation vector obtained from PS to the steepest slope direction supposing that the targeted mass movement is translational landslide; Cigna et al [32] suggested a framework for assessing landslide intensity from PSI-based matrix approach; Lu et al [33] proposed a method for quantitatively assessing landslide hazard and risk at regional scale from PS; Bianchini et al [34] showed how to use PS to improve maps of damage assessement due to landslide occurrence.…”
Section: Introductionmentioning
confidence: 99%